2016
DOI: 10.1016/j.ygyno.2016.04.219
|View full text |Cite
|
Sign up to set email alerts
|

Cerclage during trachelectomy for early-stage cervical cancer

Abstract: Low-grade endometrial endometrioid adenocarcinomas (LGEECa) can recur in the vagina (VRec), pelvic and abdominal region (PARec), or distant sites (DMet). Tumor size, histopathologic features, and lymph node involvement at presentation have been linked to the development of these recurrences. However, the amount of information on risk factors to predict site of recurrence is limited. Methods: In this multi-institutional study, we analyzed data from 589 patients with FIGO grades 1 and 2 LGEECa and found 116 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, ESGO guideline in 2018 recommended to place cerclage routinely when performing ART [14]. According to on survey of SGO members showed that 66% of surgeons agreed to place cerclage after ART [15]. All patients in our report were placed cerclage base on ESGO guideline.…”
Section: Discussionmentioning
confidence: 74%
“…However, ESGO guideline in 2018 recommended to place cerclage routinely when performing ART [14]. According to on survey of SGO members showed that 66% of surgeons agreed to place cerclage after ART [15]. All patients in our report were placed cerclage base on ESGO guideline.…”
Section: Discussionmentioning
confidence: 74%
“…If cervical cancer is diagnosed in the first trimester of pregnancy, patients should be properly counseled about the risk of continuing the pregnancy and the appropriate cancer treatment so as not to compromise either the maternal or fetal prognosis [ 51 ]. The intraoperative cerclage placed transabdominal either during FSS or subsequent pregnancy is a decision that must be made according to the patient's obstetrical history because performing a simple trachelectomy does not routinely require this procedure [ 52 , 53 ]. Performing Pap tests and/or colposcopy in patients with FSS in the first trimester in pregnant women is extremely important in diagnosing and monitoring these patients.…”
Section: Fertility-sparing Management In Cancer Patientsmentioning
confidence: 99%
“…In June of 2016, the results of an electronic survey given to all Society of Gynecologic Oncology (SGO) members were published. 3 The survey had questions regarding cerclage placement during trachelectomy for early stage cervical cancer. Of a total of 1598 Society members, 121 responded.…”
Section: Cervical Cerclage During Rtmentioning
confidence: 99%